Behavioral patterns of adults who experienced parental verbal/symbolic aggression - Gaviola, Emilyn F.; De Guzman, Ligaya S.; Ho, Leticia P.; Koo, Grace P.; Del Castillo, Lyra T. (2008)
The objectives of this study were to identify the forms of PSVA (Parental Verbal/Symbolic Aggression) that were commonly experienced by adults in their first 21 years, to estimate the intensity of hurt feelings induced by the experience of specific forms of PVSA, and to identify the current behavioral patterns of adults who experienced PSVA. Using the descriptive method, a cross-sectional survey was conducted from a randomly selected sample of 250 Filipino adults. Findings reveal that various acts of spurning and specific acts of terrorizing, exploiting, negative modeling, isolating, and denying emotional responsiveness induced intense feelings of hurt. The behavioral patterns are usually associated with the adult's symptoms of trauma, physical ailments, low self-esteem, self-sabotage, relationship problems, and difficulty handling emotions. A counseling model was proposed to help facilitate the learning and eventual healing of these adults.
Thesis (M.A. Guidance)--University of the Philippines, Diliman.
Keywords: Aggressiveness (Psychology) in adolescence -- Philippines -- Manila Metropolitan Area; Parent and adult child -- Philippines -- Manila Metropolitan Area; Child rearing -- Philippines -- Manila Metropolitan Area